Longer Contact Times Increase Cross-Contamination of Enterobacter aerogenes from Surfaces to Food - Miranda, Robyn C. (Appl Environ Microbiol, 2016)
Bacterial cross-contamination from surfaces to food can contribute to foodborne disease. The cross-contamination rate of Enterobacter aerogenes on household surfaces was evaluated by using scenarios that differed by surface type, food type, contact time (<1, 5, 30, and 300 s), and inoculum matrix (tryptic soy broth or peptone buffer). The surfaces used were stainless steel, tile, wood, and carpet. The food types were watermelon, bread, bread with butter, and gummy candy. Surfaces (25 cm(2)) were spot inoculated with 1 ml of inoculum and allowed to dry for 5 h, yielding an approximate concentration of 10(7) CFU/surface. Foods (with a 16-cm(2) contact area) were dropped onto the surfaces from a height of 12.5 cm and left to rest as appropriate. Posttransfer, surfaces and foods were placed in sterile filter bags and homogenized or massaged, diluted, and plated on tryptic soy agar. The transfer rate was quantified as the log percent transfer from the surface to the food. Contact time, food, and surface type all had highly significant effects (P < 0.000001) on the log percent transfer of bacteria. The inoculum matrix (tryptic soy broth or peptone buffer) also had a significant effect on transfer (P = 0.013), and most interaction terms were significant. More bacteria transferred to watermelon (∼0.2 to 97%) than to any other food, while the least bacteria transferred to gummy candy (∼0.1 to 62%). Transfer of bacteria to bread (∼0.02 to 94%) was similar to transfer of bacteria to bread with butter (∼0.02 to 82%), and these transfer rates under a given set of conditions were more variable than with watermelon and gummy candy. IMPORTANCE The popular notion of the “five-second rule” is that food dropped on the floor and left there for <5 s is “safe” because bacteria need time to transfer. The rule has been explored by a single study in the published literature and on at least two television shows. Results from two academic laboratories have been shared through press releases but remain unpublished. We explored this topic by using four different surfaces (stainless steel, ceramic tile, wood, and carpet), four different foods (watermelon, bread, bread with butter, and gummy candy), four different contact times (<1, 5, 30, and 300 s), and two bacterial preparation methods. Although we found that longer contact times result in more transfer, we also found that other factors, including the nature of the food and the surface, are of equal or greater importance. Some transfer takes place “instantaneously,” at times of <1 s, disproving the five-second rule.